Dynamic linkages between poverty, inequality, crime, and social expenditures in a panel of 16 countries: Two-step GMM estimates - Muhammad Khalid Anser; Zahid Yousaf; Abdelmohsen A. Nassani; Saad M. Alotaibi; Ahmad Kabbani; Khalid Zaman (Journal of Economic Structures, 2020)
The study examines the relationship between growth-inequality-poverty (GIP) triangle and crime rate under the premises of inverted U-shaped Kuznets curve and pro-poor growth scenario in a panel of 16 diversified countries, over a period of 1990-2014. The study employed panel Generalized Method of Moments (GMM) estimator for robust inferences. The results show that there is (i) no/flat relationship between per capita income and crime rate; (ii) U-shaped relationship between poverty headcount and per capita income and (iii) inverted U-shaped relationship between income inequality and economic growth in a panel of selected countries. Income inequality and unemployment rate increases crime rate while trade openness supports to decrease crime rate. Crime rate substantially increases income inequality while health expenditures decrease poverty headcount ratio. Per capita income is influenced by high poverty incidence, whereas health expenditures and trade factor both amplify per capita income across countries. The results of pro-poor growth analysis show that though the crime rate decreases in the years 2000-2004 and 2010-2014, while the growth phase was anti-poor due to unequal distribution of income. Pro-poor education and health trickle down to the lower income strata group for the years 2010-2014, as education and health reforms considerably reduce crime rate during the time period.
Keywords: C33; D63; I32; O47; 330; Pro-poor growth; Income inequality; Quality education; Healthcare expenditures; Crime rate; System panel GMM